Utility of Perioperative Peripheral Nerve Block in Tibial Plateau Fractures: An Assessment of Postoperative Pain and Other Patient Factors. Issue 1 (January 2019) - Radi, Joshua K.; Curtis, Amy B.; DiSilvio, Frank; Vangsnes, Eric; Byram, Scott; Summers, Hobie
Abstract : Background: There is a problem with opioid use in the United States. The aim of this research was to identify techniques to decrease opioid use in a specific patient population. Is perioperative peripheral nerve block (PNB) for tibial plateau fractures associated with postoperative opioid prescription, inpatient length of stay, and readmission? Methods: This was a retrospective secondary data analysis of patients between the ages of 18 and 65 years with operative tibial plateau fractures from 2006 to 2015 at a level-I trauma center. Exclusion criteria included preinjury opioid use or history of opioid dependence, an American Society of Anesthesiologists (ASA) class of ≥3, renal or lower-extremity neurological impairment, and/or rheumatoid arthritis. Three hundred and fifteen operative tibial plateau fractures were identified and, following application of our exclusion criteria, the final sample size was 216. The patients were classified as receiving a single-shot PNB versus no PNB. The main outcome measurements included total inpatient and long-term opioid use, hospital length of stay, and early follow-up, which were compared in both groups. Results: There was less total opioid use on the day of surgery (p = 0.044, t = 2.028, mean difference = 27.109 mg, 95% confidence interval [CI] [0.766 to 53.452], degrees of freedom [df] = 1) and a decrease in hospital length of stay by 2.8 days in the single-shot PNB group (p = 0.003, t = 2.990, mean difference = 2.812 days, 95% CI [0.952 to 4.672]) compared with the no-PNB group. Conclusions: Single-shot PNB may be an effective method for decreasing day-of-surgery opioid use and hospital length of stay for patients undergoing tibial plateau fracture repair compared with no PNB. Single-shot PNB did not impact readmission or long-term opioid usage compared with no PNB for tibial plateau fracture repair. Rebound pain needs to be controlled for on postoperative day 1.